2022
DOI: 10.1002/aenm.202203821
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Stability of Supercapacitors at High Voltages and High Temperatures by the Implementation of Ethyl Isopropyl Sulfone as Electrolyte Solvent

Abstract: promising technologies. [1] EDLCs display high power densities and extremely high lifetime which makes them the technology of choice for a variety of applications requiring a fast and continuous delivery of energy. However, as the energy density of these devices is rather limited (5-8 Wh kg −1 ), their use is currently limited to applications that require a relatively low amount of energy. [2] As indicated by several studies, an increase in energy density would lead to a drastic increase in the number of possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…[80] Köps et al investigated using EiPS in EDLCs at high voltages and temperatures. [81] By investigating the aged electrolyte by GC-MS and the aged electrodes by XRD and XPS, the authors propose several degradation mechanisms that coincide well with the previously mentioned works. GC-MS analysis of the aged electrolyte revealed that no soluble decomposition products originating from the solvent were formed.…”
Section: Nonconventional Organic Electrolytessupporting
confidence: 75%
See 2 more Smart Citations
“…[80] Köps et al investigated using EiPS in EDLCs at high voltages and temperatures. [81] By investigating the aged electrolyte by GC-MS and the aged electrodes by XRD and XPS, the authors propose several degradation mechanisms that coincide well with the previously mentioned works. GC-MS analysis of the aged electrolyte revealed that no soluble decomposition products originating from the solvent were formed.…”
Section: Nonconventional Organic Electrolytessupporting
confidence: 75%
“…While resulting in pore blocking and thus capacitance‐reducing effects, this layer drastically increased the electrochemical long‐term stability. [ 81 ]…”
Section: Failure Mechanisms Of Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 30 ] The inhibited hydrolysis of the acidic C2‐H position in the [EMIM] + cation or the fluorinated [BF 4 ] − anion on the hydrophilic NDSTC interface thus contributes to reduced electrolyte decomposition and improved floating stability. [ 27 ] The cycling test of the NDSTC‐IL+CO 2 device (Figure S9c–e, Supporting Information) performed at 10 A g −1 for 10 000 cycles ends with a capacitance retention over 93.2% and a coulombic efficiency close to 100%, which is higher than that of 89.4% observed for the NDSTC‐IL device. This result highlights improved cycling stability with lower contact‐ and diffusion‐resistance, and thus lower thermal stress in NDSTC‐IL+CO 2 device during fast processes.…”
Section: Resultsmentioning
confidence: 95%
“…After balancing between the high‐energy demand and the voltage stability for practical application, the voltage window of NDSTC‐IL+CO 2 device is further expanding to3.4 V (Figure S6, Supporting Information). [ 27 ] The GCPL profiles exhibit a comparable coulombic efficiency over 98.5% and a specific capacitance of 198 F g −1 at a low current density of 0.5 A g −1 , indicating that no significant side reactions are induced with higher voltages. Accordingly, the NDSTC‐IL+CO 2 electrode delivers a specific energy of 63.4 Wh kg −1 at 75.6 W kg −1 , along with a power density of 7363 W kg −1 at 53.5 Wh kg −1 within a voltage window of 3.0 V (Figure S5b, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%